Formulation of food bar based on Moringa leaves as a functional food for nursing mother - A. Ihwah; S. A. Mustaniroh; D. Pranowo (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2019)
Indonesian Statistics’ survey in February 2018 showed that the number of female labor force continues to increase every year. Currently, from 134 million (69.20%), 55.44% of them are female workers (72.25 million) with 25 million are of reproductive age. Based on Basic Health Research, the number of mothers who breastfeed their babies is only 42% far below the target of 80%. Mother can consider the amount of nutrition based on age during pregnancy and lactation. However, the food products as a substitute for heavy foods with sufficient nutrition and calories for breastfeeding mothers are currently not available. This study aimed to formulating food products for breastfeeding mothers based on the use of local raw materials such as Moringa leaves. The method used in this research was formulation using linear programming (Linear Programming Solver 1.9.4 software). A hedonic sensory test was employed to determine product acceptance with the rating scale of 1-5 in the range of very dislike to really like. The respondents consisted of 40 panelists. The results showed that the optimal formulation of food bar (in each 150 g of food bars) consisted of Moringa leaf powder (5 g), soy flour (5 g), banana flour (20 g), oat (75 g), ant sugar (22.5 g) and skim milk (22.5 g). The results from the hedonic test indicated a good acceptancefrom the respondents, with the following score: 3.68 on aroma, 3.59 on color, 4.00 on texture, 3.76 on taste and 3.73 on appearance, respectively.